Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/twec.13383
|View full text |Cite
|
Sign up to set email alerts
|

How special are special economic zones: Evidence from South Asia

Abstract: This study applies quasi‐experimental designs to assess how successful the special economic zones (SEZs) have been in offering a better investment climate than what is available to firms outside of them in three South Asian countries: India, Bangladesh and Pakistan. The World Bank Enterprise Surveys' data for 2013–2014 on multiple investment climate factors have been organised into 48 onsite and offsite investment climate variables for the assessment. The study is the first to provide causal evidence based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In South Asia, some studies assessing the impact of SEZs on export diversification have found mixed results (Aggarwal et al, 2008;Aggarwal, 2005). For example, in 2008, 40 years after the creation of SEZs, exports from Indian SEZs accounted for only 5% of overall exports; in contrast, after 2008, exports from SEZs accounted for almost a fifth and a third of exports in Bangladesh and Sri Lanka, respectively (Aggarwal et al, 2008).…”
Section: Special Economic Zones and Economic Diversification: Theoret...mentioning
confidence: 99%
See 1 more Smart Citation
“…In South Asia, some studies assessing the impact of SEZs on export diversification have found mixed results (Aggarwal et al, 2008;Aggarwal, 2005). For example, in 2008, 40 years after the creation of SEZs, exports from Indian SEZs accounted for only 5% of overall exports; in contrast, after 2008, exports from SEZs accounted for almost a fifth and a third of exports in Bangladesh and Sri Lanka, respectively (Aggarwal et al, 2008).…”
Section: Special Economic Zones and Economic Diversification: Theoret...mentioning
confidence: 99%
“…In South Asia, some studies assessing the impact of SEZs on export diversification have found mixed results (Aggarwal et al, 2008;Aggarwal, 2005). For example, in 2008, 40 years after the creation of SEZs, exports from Indian SEZs accounted for only 5% of overall exports; in contrast, after 2008, exports from SEZs accounted for almost a fifth and a third of exports in Bangladesh and Sri Lanka, respectively (Aggarwal et al, 2008). In India, Lonarkar (2014) analysing the export performance of SEZs found significant differences between particular zones in their export performance and, in many cases, SEZs did not achieve target export levels.…”
Section: Special Economic Zones and Economic Diversification: Theoret...mentioning
confidence: 99%
“…For example, some scholars suggest that SEZs display no significant economic impact on exports (Johansson & Nilsson, 1997), and the labor force skills has not significantly improved with the development of the zones over time (Sadni-Jallab & Blanco, 2002). The evaluation of the economic impact on regions is challenging due to factors such as the location, the quality of infrastructure, and regional governance, all of which can affect the performance of SEZs (Aggarwal, et al 2008).…”
Section: Special Economic Zonesmentioning
confidence: 99%
“…China's case with special economic zones is an especially well-documented success story (Schminke and Van Biesebroeck 2013;Wang 2013;Lu et al 2019). Evidence on the experiences of other developing countries are more mixed, suggesting that success is dependent on the institutional context and other initial conditions (e.g., Aggarwal et al 2008;Steenbergen and Javorcik 2017;Alkon 2018). In Indonesia, the importance of economic zones was studied by Winardi et al (2019), who found that zones contribute to attract more investment, generate employment and enhance regional economic growth in their neighborhood.…”
Section: Introductionmentioning
confidence: 99%